Personal collections held by the Royal Society (as filmed by the AJCP), [M1927-M1940] - Herschel, John F. W. (John Frederick William), Sir, 1792-1871; Royal Society (Great Britain); Australian Joint Copying Project; National Library of Australia; State Library of New South Wales (Canberra : Australian Joint Copying Project, 1699)
Records 1699-1937 of the Royal Society; Letters 1774-1820 received by Sir Charles Blagden; Correspondence 1822-1870 of Sir John F.W. Herschel; Letters 1905-1921 sent to Sir Joseph Larmor; Correspondence 1832-1859 of Sir John W. Lubbock; Photocopies of correspondence 1890-1936 of Lord Rutherford; Correspondence 1825-1873 of Sir Edward Sabine.
National Library of Australia holds microfilm master.
Filmed as part of the Australian Joint Copying Project by the National Library of Australia and the Library of New South Wales.
Australian Joint Copying Project handbook. Part 8 : Miscellaneous [M series]
Australian Joint Copying Project miscellaneous series M1927-M1940.
Digital master available
Originals held by the Royal Society Library, London.
Keywords: Herschel, John F. W. -- Sir, -- 1792-1871 -- Archives; Scientists -- Great Britain -- Archives; Astronomy -- Australia; Scientific expeditions -- Antarctica; Science -- Pacific Area